2014
DOI: 10.1111/sms.12375
|View full text |Cite
|
Sign up to set email alerts
|

Community size and sport participation across 22 countries

Abstract: The objective of this study was to examine, across 22 countries, the association between community size and individual sport, team sport, and exercise participation. Hierarchal non-linear Bernoulli modeling is used to examine the association between community size (100,000-10,000; <10,000) and (a) individual sport, (b) team sport, and (c) exercise participation. After controlling for country-level clustering and demographic variables, those residing a community with between 100,000 and 10,000 residents are mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
2
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 23 publications
0
5
2
3
Order By: Relevance
“…For example, an Australian survey reported that less (Eime et al, 2016). While age is known to be negatively associated with PA (Balish, Rainham, & Blanchard, 2015;Eime et al, 2016;Fernandes & Zanesco, 2010); we found no evidence of a decrease in sports participation over the follow-up period.…”
Section: Discussioncontrasting
confidence: 75%
“…For example, an Australian survey reported that less (Eime et al, 2016). While age is known to be negatively associated with PA (Balish, Rainham, & Blanchard, 2015;Eime et al, 2016;Fernandes & Zanesco, 2010); we found no evidence of a decrease in sports participation over the follow-up period.…”
Section: Discussioncontrasting
confidence: 75%
“…Household composition and specifically having active children in the household increases participation but having children who are not active and are under the age of 6 decrease participation, particularly among single parents (Scheerder & Vos, 2011;. Those who are native to the country of residence (Breuer, Hallmann, & Wicker, 2011;Ruseski, Humphreys, Hallmann, & Breuer, 2011) and those who work at the managerial level and above show higher sport participation rates than their counterparts (Stamm & Lamprecht, 2011;, while people living in urban areas show higher participation levels than those living in rural areas (Garcia, Lera-Lopez, & Suarez, 2011;Balish, Rainham, & Blanchard, 2015). However, recent empirical evidence from Australia suggests the opposite relationship (Eime, Harvey, Charity & Payne, 2016).…”
Section: Sports Participation: Driversmentioning
confidence: 99%
“…A cross-sectional study of Australians aged 15 and older showed that participation in many team sports increased as socio-economic status decreased and geographical remoteness increased 42) . Regarding environmental factors, those who live in communities with between 10,000 and 100,000 residents were more likely to participate in team sports than those who live in communities with more than 100,000 residents 43) . As for neighborhood safety, those who perceived neighborhood social safety participated in sports at indoor sports clubs more often than those who did not 44) .…”
Section: Determinants Of Participation In Group Exercisementioning
confidence: 99%